Effectiveness of online expressive writing in reducing psychological distress among the asymptomatic COVID-19 patients in Fangcang Hospitals: A quasi-experiment study - Zheng, Xican; Qu, Jingrui; Xie, Jun; Yue, Wei; Liang, Xuejun; Shi, Zhen; Bai, Jing; Sun, Zhiyan; Cheng, Fangna; Li, Xiaoxia; Liu, Chunxia (Frontiers in Psychology, 2023)
Objective This study aimed to assess the applicability and effectiveness of an online format of expressive writing (EW) in reducing psychological distress among the asymptomatic COVID-19 patients in Fangcang Hospitals with a quasi-experiment. Method Altogether 244 patients were assigned to the EW group(n=122) and the control group(n=122). Besides the routine psychological intervention (broadcast relaxation training at a fixed time) in Fangcang hospitals, The EW group was engaged in 8-day theme-based adaption EW intervention, whereas the control group received no interventions. All the participants were tested with the Brief Profile of Mood States (BPOMS) and Inpatient Mental Health Preliminary Screening Scale(IMHPS) before and after the intervention. After the intervention, the writing quality and intervention satisfaction of the EW group were evaluated by a self-designed writing quality questionnaire and EW satisfaction questionnaire. Results The results indicated that the EW significantly improved in the BPOMS test, whereas the control group showed no significant change. The IMHPS score in the control group was statistically deteriorated than that before intervention, whereas the EW group showed no significant change. The writing quality was highly correlated with the score change of BPMOS. The overall satisfaction of patients with EW was 81.13%. Conclusion EW can reduce psychological distress among the asymptomatic COVID-19 patients in Fangcang Hospitals. The higher the quality of writing, the greater the improvement of mood states. As a new form of psychological intervention in Fangcang hospitals with high patient satisfaction, EW has a value of popularization and application.